Effects of Inspiratory Muscle Training with and without Resistance Training on Functional Capacity and Quality of Life in Patients with Phase II Cardiac Rehabilitation - Maham Ashfaq, Qurat Ul Ain, Mohsana Tariq, Misdaq Batool, Sidra Faisal, Tamjeed Ghaffar, Zara Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Inspiratory muscle preparing is a protected mediation in early postoperative period which cause enhancements in utilitarian limit and respiratory muscle strength might lead patients to take part in exercises of everyday living. Objective: The objective of study was to determine the effects of Inspiratory muscle training with and without resistance training on Functional capacity and quality of life in patients with phase II cardiac rehabilitation. Methods: It was randomized controlled trial. Data was collected from Dr. Zia ul Rehman Heart Center, Chiniot. 20 subjects Aged between 40-60 years were randomized in this study design. Cardiac Patients, Undergoing Cardiac surgery Patients, Patients undergoing CABG at least 3 weeks prior and Presently non-smokers were included in the study. Clinical course without complications during hospital stay was scored on Glittre-ADL test and Minnesota living with heart failure questionnaire before and after end of treatment session. Upper and lower limb resistance training was performed for 20 minutes, with 3 sets of 10 repetitions. Results: Independent sample t-test was applied to compare pre-treatment and post-treatment Minnesota Living with Heart Failure Questionnaire here was statistically significant difference between two groups with P < 0.05. Comparison of Glittre-ADL test within each treatment group applied paired sample t-test which showed statistically important variation for both groups (P< 0.05) with greater difference seen in group Inspiratory Muscle Training with Resistance Training. Comparison of MLHFQ within each treatment group applied paired sample t-test which showed statistically important variation for both groups (P< 0.05) with greater difference seen in group Inspiratory Muscle Training with Resistance Training. Practical Implication: it was shown that CABG patients whose personal satisfaction, uneasiness, and sorrow were undeniably diminished subsequent to taking part in inspiratory muscle preparing. Conclusion: Inspiratory muscle training with resistance training is more effective on functional capacity and quality of life in patients with phase II cardiac rehabilitation. Keywords: Inspiratory Muscle Training, Resistance training, Functional capacity, Cardiac rehabilitation.